Graphic symbol practices as a whole school approach in two inclusive primary schools in England and Cyprus - Pampoulou, Eliada (My University, 2016)
BACKGROUND: Graphic symbols have been traditionally used in special education schools, but with inclusion on the education agenda their usage has been introduced in many mainstream schools as well. However, there is scant literature exploring the factors that influence the implementation of these symbols as a whole school approach. OBJECTIVE: To uncover the factors that promote or impede the use of graphic symbols usage at the whole school level in inclusive primary schools. METHODS: Two inclusive primary schools, in England and Cyprus, were identified via a postal survey. Following the phenomenology of pedagogy, the data were collected through semi-structured interviews, close observations, visual evidence of symbol use and the researcher keeping a reflective journal. The data were subject to thematic analysis with the themes being drawn from the aide-mémoire. RESULTS: Factors that promote the usage of graphic symbols are the knowledge and expertise of those using them and the leader s good managerial skills and the latter s professional role. Factors that can impede the usage of graphic symbols include the classroom teachers negative attitudes and lack of time. CONCLUSION: Individuals who are graphic symbol champions need to be given the authority to influence existing practices in the schools.
Keywords: Classroom teachers; Graphic symbols; Inclusive education; Special education; Special educational needs coordinator (SENCo)